Reliability‐based non‐linear analysis according to fib Model Code 2010. (7th March 2013) - Cervenka, Vladimir
Abstract The fib Model Code 2010 for Concrete Structures introduces numerical simulation as a new tool for designing reinforced concrete structures. The model of resistance based on non‐linear analysis requires adequate model validation and a global safety format for verifying designs. The numerical simulations combined with random sampling offer the chance of an advanced safety assessment. Approximate methods of global safety assessment are discussed and compared in a case study. An example of a bridge design supported by non‐linear analysis is shown.